Natural Phenomena in the Systematic Patterns of the Fibonacci Sequence and Fractal Patterns in the Context of Educational Philosophy - Sri Mariana; Rayandra Asyhar; Asrial Asrial; Syaiful Syaiful (Edumaspul: Jurnal Pendidikan, 2025)
This research aims to describe the relationship between natural phenomena as reflected in the Natural Phenomena in the Systematic Pattern of the Fibonacci Sequence and Fractal Patterns in the Context of Philosophy of Education, particularly in the aspects of ontology, epistemology, and axiology in mathematics learning. The types of research used are descriptive research and library research. The findings in this article are that mathematical concepts such as the Fibonacci sequence and fractal patterns can be integrated into philosophy-based education learning. Natural patterns such as the Fibonacci sequence and fractals in mathematics teaching not only deepen the understanding of mathematical concepts ontologically but also enrich the reasoning process (epistemologically) and learning values (axiologically). This integration contributes to more contextual, relevant, and meaningful learning. The conclusion of this study emphasizes the importance of applying structured educational philosophy in mathematics teaching through the exploration of natural phenomena, thereby encouraging the development of students' understanding and critical thinking skills. This study recommends strengthening the integration of educational philosophy aspects in mathematics material through a systematic study of natural phenomena